2019
DOI: 10.1017/s0007123418000601
|View full text |Cite
|
Sign up to set email alerts
|

Personnel Politics: Elections, Clientelistic Competition and Teacher Hiring in Indonesia

Abstract: What is the effect of increased electoral competition on patronage politics? If programmatic appeals are not credible, institutional reforms that move politics from an elite- to a mass-focused and more competitive environment increase patronage efforts. This leads to an overall surge and notable spike in discretionary state hiring in election years. The study tests this prediction in the context of Indonesia’s decentralized education sector. The authors exploit the exogenous phasing in and timing of elections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 91 publications
(128 reference statements)
1
35
0
Order By: Relevance
“…One consequence of central recruitment of teachers is national political influence in the process. In Indonesia, the recruitment of contract teachers and promotions of civil service teachers increase during election years (Pierskalla and Sacks 2019). A similar electoral teacher recruitment cycle occurs in India (Fagernäs and Pelkonen 2018).…”
Section: Recruitmentmentioning
confidence: 78%
“…One consequence of central recruitment of teachers is national political influence in the process. In Indonesia, the recruitment of contract teachers and promotions of civil service teachers increase during election years (Pierskalla and Sacks 2019). A similar electoral teacher recruitment cycle occurs in India (Fagernäs and Pelkonen 2018).…”
Section: Recruitmentmentioning
confidence: 78%
“…He similarly argues that politicians exchange these -mainly lowranked -positions with party activists. Pierskalla and Sacks (2019) shows that the introduction of elections increased the number of teachers employed in Indonesia. In contrast, much of the seminal literature on the state suggests that electoral competition can constrain runaway state building and incentivize politicians to support meritocracy (O'Dwyer, 2006;Geddes, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…My theoretical approach also sheds light on what appear to be inconsistent findings regarding the effect of electoral competition on patronage hiring. While many scholars assert that competition can promote meritocracy (Geddes, 1994;Ting et al, 2013), others find that competition can encourage clientelism, and swell the ranks of the public sector (Pierskalla and Sacks, 2019;Driscoll, 2017;Lindberg, 2003). My theory suggests that electoral competition may have both of these effects: it may dissuade politicians from interfering in hiring for high-ranked positions, while encouraging them to recruit partisans to low-ranked positions.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The same study also found that the teacher certification process was affected by politics, in particular, local election cycles. Pierskalla and Sacks (2016) observed that since the pilkada system was introduced to promote local electoral accountability, a large number of new contract teachers (about 1,200 per district) and civil servant teachers are hired before an election. Pierskalla and Sacks note that mass hiring of new teachers may have had a negative effect on student learning.…”
Section: Challenges In Education and Training And Employmentmentioning
confidence: 99%